2020
DOI: 10.1002/pc.25888
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of bamboo fiber with sodium hydroxide and graphene oxide in epoxy composites

Abstract: Bamboo fibers (BFs) have high mechanical properties and are candidate reinforcement for epoxy matrix composites. However, to improve performance, good fiber‐matrix interaction is required. In this work, unidirectional long BF reinforced epoxy composites at fiber volume content of 22%, 40%, and 50% were made by compression molding. The 40 v% untreated BF reinforced composites exhibited 107% and 439% increase for flexural strength and modulus, respectively, compared to neat epoxy. Sodium hydroxide (NaOH) treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…6,52 Untreated bamboo natural fiber reinforced epoxy matrix composite was also found to exhibit little matrix adhering leading to gaps and interfacial debonding between the composite constituents. 53 Such spaces do not support effective stress transfer from the matrix hence, results in diminishing tensile strength of the composite relative to neat PP matrix. Also, traces of fiber pull-outs 52 can be seen in the micrograph represented by point 3, evidencing points of weak fiber-matrix adhesion.…”
Section: Morphological Analysis Of Pp/rh and Pp/rha Compositesmentioning
confidence: 99%
“…6,52 Untreated bamboo natural fiber reinforced epoxy matrix composite was also found to exhibit little matrix adhering leading to gaps and interfacial debonding between the composite constituents. 53 Such spaces do not support effective stress transfer from the matrix hence, results in diminishing tensile strength of the composite relative to neat PP matrix. Also, traces of fiber pull-outs 52 can be seen in the micrograph represented by point 3, evidencing points of weak fiber-matrix adhesion.…”
Section: Morphological Analysis Of Pp/rh and Pp/rha Compositesmentioning
confidence: 99%
“…In this work, bamboo fibres were extracted based on a hybrid mechanical-chemical method using sodium hydroxide (NaOH). The alkali solution allows the extraction of technical fibres due to the solubilization of hemicelluloses and lignin [31,32]. Moreover, this treatment increases the accessibility of the free hydroxyl groups on the fibre surface, allowing physical interactions with the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this treatment increases the accessibility of the free hydroxyl groups on the fibre surface, allowing physical interactions with the polymeric matrix. It also produces a rougher surface topography which favours interactions with the matrix [31,33]. In fact, this situation optimizes stress transfer at the fibresmatrix interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its usage, natural fiber has problems like weak interfacial bonding with matrix, poor wettability, and high moisture absorption, which can lower the strength of composite materials. [11][12][13] The surface treatments on fibers before production can solve those problems. The consequence of alkali treatment on the interfacial and mechanical behavior of coir fiber biodegradable composites was investigated by Nam et al, [14] who found that treating coir fibers with 5 wt% NaOH for 72 h enhanced surface roughness and wettability of coir fiber.…”
Section: Introductionmentioning
confidence: 99%